2014
DOI: 10.1017/s0007114513004030
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnant women living in the South East of the UK: the influence of diet and nutritional supplements on iodine status

Abstract: Iodine is a key component of the thyroid hormones which are crucial for brain development. Adequate intake of iodine in pregnancy is important as in utero deficiency may have lifelong consequences for the offspring. Data on the iodine status of UK pregnant women are sparse, and there are no such data for pregnant women in the South East of the UK. A total of 100 pregnant women were recruited to a cross-sectional study carried out at the Royal Surrey County Hospital, Guildford, at their first-trimester visit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
98
7
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 48 publications
22
98
7
3
Order By: Relevance
“…Several recent studies have suggested suboptimal iodine status in pregnant women living in areas with only partial coverage of iodized salt, such as Italy, the UK and the USA (25)(26)(27) . In a limited number of studies, long-term iodization before pregnancy showed more favourable effects on thyroid function than did short-term iodization and the early initiation of iodine supplements was more effective than beginning treatment in late pregnancy (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested suboptimal iodine status in pregnant women living in areas with only partial coverage of iodized salt, such as Italy, the UK and the USA (25)(26)(27) . In a limited number of studies, long-term iodization before pregnancy showed more favourable effects on thyroid function than did short-term iodization and the early initiation of iodine supplements was more effective than beginning treatment in late pregnancy (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the United Kingdom, the United States and Italy, areas known for partial coverage of iodised salt, also suggest suboptimal iodine status in pregnant women (Marchioni et al, 2008;Bath et al, 2014;Hollowell et al, 1998). This deficiency can occur during pregnancy, when the maternal need for thyroid hormone increases due to the transfer of iodine and thyroid hormone to the foetus and the increase in renal iodine clearance (Zimmermann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women using I supplements had a higher median UIC than non-supplement users (126 v. 66 µg/l, respectively). A UK study of 100 pregnant women found a similar median UIC of 85·3 µg/l, being higher in I supplement users than in non-supplement users (111 v. 61 µg/l, respectively) (20) . A UK study of educated women of childbearing age (n 57) found a median UIC of 63·1 µg/l (21) , remarkably similar to a comparable New Zealand study in 2010 of fifty highly educated women who had a median UIC of 65 µg/l (17) .…”
mentioning
confidence: 89%
“…Pregnant women 100 85·3-whole group Bath et al (20) 34 85-whole group Brough et al (15) 111-supplement users 126-supplement users 61-non-supplement users 66-non-supplement users Women of childbearing age 57 63·1 Bath et al (21) 50 65 Shukri et al…”
mentioning
confidence: 99%